Antigua and Barbuda. Significant achievements 2015 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Antigua and Barbuda during 2015 are identified, with respect to the needs and interests of the country, strengthening issues such as agricultural health, market research, financing and vermiculture. Finally, the structure of the commercial instance and feasibility studies were supported.